Formulation of Jakaba fertilizer from banana peel, pineapple peel, tea dregs for enhanced pak choi (Brassica rapa subsp. Chinensis) growth - Muttaqin, Salwa Zainum; Mamangkey, Jendri; Silalahi, Marina; Mendes, Lucas William (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2025)
Excessive use of chemical fertilizers can lead to environmental degradation and increase the financial burden on farmers. As a sustainable alternative, liquid organic fertilizer (LOF) derived from Jakaba (also known as jamur keberuntungan abadi) was fermented using common organic wastes. This study aimed to evaluate the effects of different organic waste substrates on the characteristics of Jakaba-based LOF (JLOF) and the growth performance of pak choi (Brassica rapa subsp. Chinensis). A completely randomized design (CRD) was used, consisting of nine treatments with three replications each. The concentration variations of banana peel waste, pineapple peel, and tea grounds used in fermentation include 100 g, 200 g, and 300 g. Observations were conducted in three time intervals on days 0, 14, and 30. Parameters measured included the physical and biological characteristics of the LOF (i.e., pH and fungal growth), as well as plant height, leaf number, and fresh weight of pak choi. The data obtained were analyzed statistically using ANOVA analysis. The results showed that tea dregs provided the most favorable conditions for Jakaba growth and maintained the most stable pH. In contrast, pineapple and banana peels inhibited fungal growth, likely due to the presence of inhibitory compounds such as tannins and bromelain. Field application on pak choi indicated that JLOF derived from tea dregs promoted the best plant growth among all groups. These findings suggest that Jakaba-based LOF formulated with tea dregs holds promise as an effective organic fertilizer and may be further developed for commercial use.